Asuhan Keperawatan Jiwa Pada Pasien Gangguan Persepsi Sensori: Halusinasi Pendengaran Dengan Pemberian Intervensi Membaca Surat Al-Fatihah Di Yayasan Rehabilitasi Mental Griya Bakti Medika Semanan 2024 - Umi Salamah; Ayu Pratiwi; Mentari Mentari (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Disturbance soul or mentally experiencing significant increase, according to WHO 2023 Mental disorders with Hallucinations in Indonesia as much as 9.8% to 10.35% occurred in DKI Jakarta. Hallucinations is affecting mental disorders function perception or perception to environment without any real stimulus so that interpret something that doesn't real without stimulus or stimulation from outside (Stuart, 2021). One of method divert hallucinations with Application Intervention read Surah Al- Fatihah besides giving therapy pharmacology. Objective Work Scientific: Knowing the Application of Nursing Care to Hallucination Patients by Providing Al- Fatihah Reading Intervention Against Changes in Sensory Perception. Method: work scientific This use method study data collection case in a way observation, interviews, documentation, as well as using study instruments case with the Fostering format Nursing And Intervention Reading Al- Fatihah. Results: Results Work scientific end Nurse obtained analysis Care Nursing after done intervention for 6 days obtained that Action nursing And innovation intervention get results positive, symptom hallucinations client experience decline And ability client divert with read Surah Al- Fatihah increase, client capable do interventions taught _ in a way independent And with correct procedure. _ Role nurse in handle hallucinations patient in the orphanage or at home Sick Wrong the only one do application Intervention Reading Surah Al- Fatihah. Conclusion: After SP was carried out for 6 days and the Al- Fatihah reading therapy showed that the client remained in the controlling phase where in this phase the client had signs of moderate scale auditory hallucinations, which means the client still had hallucinations that were controlled by intervention. read Surah Al- Fatihah based on measurements using PSYRAT.